Repercussões e percepções de mulheres submetidas à episiotomia - Nascimento, Joanne de Paula (2018)
The birth initially seen as a physiological event in a woman's life, with the advancement of technology becomes technical and institutionalized procedure. With this, many interventions were adopted routinely and indiscriminately, with episiotomy being one of them. The objective of this study is to describe the experience of women submitted to episiotomy / episiorrhaphy after the late puerperium. This is an exploratory, descriptive study with a qualitative approach, based on field research. The data were collected in two moments, the first with the application of an evocation questionnaire, which were requested for first and third person transmission and, respectively, gathered in a database processed in the EVOC software. At the end of this stage, a total of 10% of women participated in an open-ended in-depth interview, whose contents were transcribed in full and the text formatted in a single corpus for reading in the IRAMUTEQ software, in the option Hierarchical Descending, with emission of the result in the format of Dendogram. Young women with full secondary education participated. From the evocations issued, there is a coincidence of the signs that make up the upper left quadrant of the four-house picture, regardless of whether they are said in the first or third person, namely Pain and Need, these supposedly the elements of the central nucleus of the representation of the object studied, seen that in general, the other evocations support the representations contained in the central nucleus. However, they point to some change in this, the issue in the name of the term impotence, this as an element of the second periphery, and said in the third person, the expression lack information, which appears as an element of contrast, and in the second periphery, terms which point to the negative genital image after the procedure. The textual part analyzed resulted in the dendogram with two axes which classified the approaches related to aspects of living as a woman and maternal experience. In the first axis appear two classes, one with content relative to the aspect sexuality, and the other about the personal feelings. The second axis has a class, which portrays the maternal feelings. The episiotomy appears in the speech as a procedure little known before the experience lived, however understood as necessary for the positive outcome of childbirth. Despite this, it is perceived as a negative experience, due to physical and emotional pain, distortion of the genital image, and consequent difficulty to return to active sexual life. It is of fundamental importance that there is a change in obstetric care to make childbirth safer and to improve the quality of women's experience in the process of parturition.